2009
DOI: 10.1002/cphc.200800565
|View full text |Cite
|
Sign up to set email alerts
|

Positron Annihilation Lifetimes in Cucurbiturils: Evidence of Internal Inclusion of Gold in CB[7]

Abstract: Positron annihilation lifetime (PAL) measurements are carried out to determine the cavity dimensions of hydrated and dehydrated cucurbiturils (CB[n]; n=5,6,7,8). In the case of hydrated samples, the dimensions of the cavity are unrelated to the number of glycoluril units of the CB, whereas for dehydrated samples the cavity dimensions measured by PAL follow the expected order, although the experimental values obtained by PAL are significantly smaller than the dimensions of each CB determined by crystallography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…378 Garcı ´a then used positron annihilation lifetime measurements to show that the free volume of CB [7] decreased when interacting with small Au NPs, in accordance with the assumption that the NPs can sit within the cavity of the macrocycle. 379 The same author also showed that photolysis of Au@CB [7] at 532 nm affords an intense transient spectrum generated upon electron ejection from excited Au clusters, which decays well past 1.6 ms; CB [7] hinders electron-hole recombination between the Au clusters, and no transient is detected with larger Au NPs, as expected. 380 Irradiated Au@CB [7] NPs were also found to enhance the rate of dimerization of phenylacetylene to 1,3-diphenylbutadiyne by a factor of 7, since light generates positively charged Au clusters that promote the reaction.…”
Section: Polymers Cb[n]mentioning
confidence: 59%
“…378 Garcı ´a then used positron annihilation lifetime measurements to show that the free volume of CB [7] decreased when interacting with small Au NPs, in accordance with the assumption that the NPs can sit within the cavity of the macrocycle. 379 The same author also showed that photolysis of Au@CB [7] at 532 nm affords an intense transient spectrum generated upon electron ejection from excited Au clusters, which decays well past 1.6 ms; CB [7] hinders electron-hole recombination between the Au clusters, and no transient is detected with larger Au NPs, as expected. 380 Irradiated Au@CB [7] NPs were also found to enhance the rate of dimerization of phenylacetylene to 1,3-diphenylbutadiyne by a factor of 7, since light generates positively charged Au clusters that promote the reaction.…”
Section: Polymers Cb[n]mentioning
confidence: 59%
“…A drop of a suspension of the CB encapsulated gold was placed on a conductive graphitized grid. Full characterization details of Au@CB[7] sample have been already reported by us in refs and .…”
Section: Methodsmentioning
confidence: 99%
“…In 2007, using CB[ n ]s ( n = 5, 6, 7, 8) as protecting agents for the first time, Corma and Lee et al [ 24,45 ] added NaBH 4 to CB[ n ]s and HAuCl 4 mixture in water/ethanol, yielding CB[ n ]s‐protected AuNPs with various sizes (diameter from 1.2 to 10 nm). The extremely stable AuNP assemblies with CB[ n ]s as the glue could also be in situ obtained, generating 1 nm gap between adjacent NPs.…”
Section: Synthesis Approaches Of Cb[n]s‐mediated Nmnpsmentioning
confidence: 99%
“…[ 11b ] For instance, AuNCs encapsulated inside CB[7] cavity with the average diameter of 1 nm, could produce intense transient absorption spectrum upon 532 nm excitation in water. [ 45b ] This light induced long‐lived charge separation process along with electron ejection from photoexcited AuNCs to others or the solvent. The charged AuNCs possess luxuriant active catalytic sites, which significantly affect the catalytic activity.…”
Section: Applications Of Cb[n]s‐mediated Nmnpsmentioning
confidence: 99%